ANALISIS PESAN KOMUNIKASI ISL AM DALAM KITAB MUKHTASOR IHYA' ULUMUDDIN KARYA IMAM AL-GHAZALI - Sri Wahyuni; Nur Ainiyah (Fakultas Dakwah Universitas Ibrahimy, 2026)
This study analyzes the Islamic communication messages contained in the book Mukhtasor Ihya' Ulumuddin by Imam al-Ghazali. This book is a summary of Ihya' Ulumuddin and encapsulates the essence of comprehensive Islamic teachings, covering aspects such as aqidah (creed), sharia (Islamic law), and akhlaq (ethics). The primary focus of this research is to identify and understand how al-Ghazali formulates and conveys religious messages through his use of language, argumentative structure, and narrative style. The study aims to conceptualize the Islamic communication messages found within Mukhtasor Ihya' Ulumuddin. A qualitative content analysis method was employed, utilizing a descriptive-analytical approach to the text. The findings indicate that the Islamic communication messages in Mukhtasor Ihya' Ulumuddin are characterized by the use of persuasive and profound language and an emphasis on the correlation between knowledge and action.